Circular causality in volition - Liljenström, Hans (Frontiers in Network Physiology, 2025)
Conventional scientific paradigms predominantly emphasize upward causality, often overlooking or dismissing the role of downward causality. This approach is also prevalent in neuroscience, where cortical neurodynamics and higher cognitive functions are typically viewed as consequences of neuronal or even ion channel activity. Conversely, mental phenomena are generally assumed to lack causal efficacy over neural processes—an assumption that is increasingly being questioned. The causality associated with volition may be analyzed at three organizational levels: (1) neuronal interactions within cortical networks, (2) interregional dynamics between distinct brain areas, and (3) the reciprocal relationship between the nervous system and its environmental context. Across all these domains, circular rather than strictly linear causality appears to be at play. This paper examines the implications of such circular causality for volition and the longstanding problem of free will, with particular reference to insights derived from neurocomputational modeling.